BENTUK DAN PERBEDAAN MAKNA [UCHI NI], [AIDA NI], DAN [KAGIRI] YANG BERFUNGSI SEBAGAI SETSUZOKUSHI DALAM NOVEL RYOMA GA YUKU KARYA RY?TAR? SHIBA - Anggaraini, K Nastya (Humanis; Volume 12. No.1. Juli 2015, 2015)
This research was analyzing about form and the different meaning of [uchi ni], [aida ni], and [kagiri] as a conjunction in a novel by Ry?tar? Shiba entitled “Ryoma ga Yuku”. The result of this research showed that in the sentences contains [uchi ni], [aida ni], and [kagiri] can form by adding verb, adjective, or noun in front of those conjunctions. [Uchi ni] and [aida ni] is similar but they have their own meanings. Similar with [uchi ni], [aida ni] shows two situations in one time and because of that situations there is a change in that situation. [Aida ni] can shows a long and short time of a situation but [uchi ni] just shows a short time of situation. [Kagiri] shows a term when a situation can happen.
Keywords: [uchi ni], [aida ni], [kagiri]